Reclaiming Palestinian History: An Analytical Study of Ancient Arabic Language - Yaacob, Solehah@Nik Najah Fadilah; al-Sa'adi, Abdul Razak Abdul Rahman Asaad; Yeob, Shamsul Jamili (2010)
Palestinian history has become one of the most obfuscated histories of today as a result of the stranglehold on the study of Palestine and the ancient Near East. Palestinian history has been denied a place in western academic discourse. This research approaches ancient Palestinian history based on linguistic theory, i.e. the analytical and critical study of ancient Arabic language. The question is how linguistic theories can contribute to reclaim the history of Palestine. It is assumed that a critical reassessment of the origin of Palestinian history is possible through the study of ancient Palestinian linguistics. An academic linguistic approach ensures that the study of languages is integrated into a larger context. It aims at introducing Palestinian history as a more readily accessible field of study no longer monopolized by exclusivist biblical studies. When we relate Islamic literature to predating ancient eastern religions and history as major sources of reference rather than referring to Jewish and Christian sources, we have to investigate the authenticity of their views. In order to gain a comprehensive understanding of the development of Arabic ancient civilization, the researcher considers it essential to assess linguistic theories developed by Muslim scholars. Major primary sources constitute the extant ancient scriptures which reflect the stages of ancient eastern civilization. The first part of our analysis addresses linguistic theory focusing on the plethora of documented social interaction of various ancient Near Eastern societies. The history of ancient Palestine has been continuously sidelined by the domineering branch of biblical studies focusing on the history of ancient Israel, and thus, in order to restore balance, it is imperative to give the study of Palestinian history back its identity as „Arab history‟.